Pengembangan multimedia Tata Surya berbasis Articulate Storyline untuk meningkatkan literasi sains Kelas VI SD - Prabawa, Agung; Maryani, Ika (Berkala Fisika Indonesia : Jurnal Ilmiah Fisika, Pembelajaran dan Aplikasinya, 2024)
Development of Solar System based multimedia Articulate Story to improve science literacy for Class VI Elementary School. This research aims to develop a multimedia Solar System based on an Articulate Storyline oriented toward scientific literacy. This research is development using the ADDIE model. The research subjects were 1 media expert, 1 material expert, 1 learning expert, 1 language expert, 1 teacher, and 19 students. Data was taken using questionnaires and tests. The data collection instruments used were validation assessment sheets, response questionnaire sheets, and questions pretest-posttest. Effectiveness test on 19 students with one group pretest-posttest design. Collecting scientific literacy data with validated questions of 10 multiple choice questions. The research results show that quality assessments from media experts, material experts, learning experts, and language experts show that the media is of high quality. The teacher responded well as shown in the results of filling out the response questionnaire and the students responded well to the media by giving positive responses to the response questionnaire that had been given. The effectiveness testing results show that the solar system is based on multimedia Articulate Storyline effective in increasing scientific literacy in grade VI elementary school. Students' interest in multimedia learning is visible, with their active interaction increasing learning success, showing the effectiveness of multimedia in improving the learning process.